133 Incidence of Imaging Confirmed Stroke and Thrombotic Events in Older Adults with Severe COVID-19 Infection. (16th March 2021) - Hickmott, L; Jeyarajah, C; Logarajah, S; Webber, A; Epstein, D; Qureshi, S; Penge, J
Abstract: : During the initial phase of the response to COVID-19, concern was raised regarding a potential link with increased risk of stroke. We aimed to explore the incidence of stroke and thrombotic events within our local population with COVID-19 infection who required admission to the Intensive Care Unit (ICU). Methods: Retrospective analysis of 57 consecutive patients with a diagnosis of COVID-19 infection admitted to Barnet General Hospital ICU between 6th March and 26th April 2020. Cases were reviewed to establish whether there had been imaging (CT or MRI) confirmed ischaemic stroke, intra-cerebral haemorrhage (ICH), venous sinus thrombosis (VST) or other thrombotic event, including pulmonary embolism (PE). Data was collected on baseline characteristics and blood tests including D-Dimer levels. Statistical analysis was performed using two-tailed t-test and Fischer's exact test (FET). Findings: Nineteen patients (33%) were age 65 years or older (mean age 69, range 65 to 74 years) and of these 2 patients (10.5%) had imaging confirmed acute ischaemic stroke. In those under 65 (mean age 54, range 29–64 years) there was one confirmed ICH and one VST. The incidence of PE was 21% in both groups. Survival was significantly lower in the age 65 or older group (26.3% versus 63.2%, p = 0.0119 (FET)). Peak recorded D-Dimer levels also appeared to be significantly higher in the age 65 or older group (p = 0.0003, 95% CI 13068.89 to 39858.68). Conclusions and limitations: These findings highlight the importance of awareness of risk of thrombotic events, including acute stroke, in older adults with severe Covid-19 infection. It is possible that the incidence of stroke was underestimated, including due to challenges identifying clinical signs of acute stroke and safely obtaining imaging in this population. Further, ideally prospective, studies are required to more clearly elucidate the degree of association between COVID-19 infection and stroke and VST.